A pirataria como campo de possibilidades: apropriações materiais e simbólicas em diferentes sentidos - Fernanda Martinelli (Ciências Sociais Unisinos)
This article discusses situations observed in a survey previously conducted on the consumption of luxury pirated goods. Representative fragments are gathered to help us think about (i) the relation of social classes, especially urban middle classes, through the consumption of famous brands and its connection to the piracy of goods; and (ii) how the objects, functioning as supports for these emblems, are immersed in social relations, how they are made available and accessed, and how the interactions around them occur. Also, we propose to reflect on the production of different contexts in which piracy intervenes with life trajectories, applying the notion of field of possibilities as presented by Gilberto Velho (2003b). We observe how the dimensions of consumption, work and production, although connected, display specific meanings about piracy that impact on the formulation of individual projects and on the social production of difference.